Variable NK cell receptors exemplified by human KIR3DL1/S1 - Parham, Peter; Norman, Paul J; Abi-Rached, Laurent; Guethlein, Lisbeth A (The Journal of immunology (1950), 2011)
Variegated expression of variable NK cell receptors for polymorphic MHC class I broadens the range of an individual's NK cell response and the capacity for populations and species to survive disease epidemics and population bottlenecks. On evolutionary time scales, this component of immunity is exceptionally dynamic, unstable, and short-lived, being dependent on coevolution of ligands and receptors subject to varying, competing selection pressures. Consequently these systems of variable NK cell receptors are largely species specific and have recruited different classes of glycoprotein, even within the primate order of mammals. Such disparity helps to explain substantial differences in NK cell biology between humans and animal models, for which the population genetics is largely ignored. KIR3DL1/S1, which recognizes the Bw4 epitope of HLA-A and -B and is the most extensively studied of the variable NK cell receptors, exemplifies how variation in all possible parameters of function is recruited to diversify the human NK cell response.